Association Between Red Cell Distribution Width (RDW)/Platelet Ratio and Degree of Fibrosis in Patient with Chronic Hepatitis B - Yaditta Mirdania; I Ketut Mariadi; IDN Wibawa (The Indonesian Society for Digestive Endoscopy, 2018)
Background: Histological examination of the liver remains the gold standard of assessing liver cirrhosis. However, this examination is an invasive method with many complications. This study aims to determine therelationship between degree of liver fibrosis with red cell distribution width (RDW)/platelet ratio which can then be used as non-invasive diagnostic method of liver fibrosis.Method: This was a retrospective study, the data of hematological profiles including hemoglobin, RDW, and platelet was taken from medical records of all chronic hepatitis B patients undergoing Fibroscan at Sanglah Hospital in January 2016 to February 2017.Results: Of 58 patients, 10 patients was excluded due to chronic kidney disease, malignancy and coincide with hepatitis C and HIV. The analysis using Kruskal-Wallis test, found a significant relationship betweenRDW/platelet ratio with degree of fibrosis in chronic hepatitis B (p 0.05). Of the 48 patients, 23 patients with mild-moderate fibrosis (metavir F0-2) and 25 patients with severe fibrosis (metavir F3-4) were found. In ROCanalysis, the AUC was 0.734, using cut off 0,065 RDW/platelet ratio predict severe fibrosis about 7% sensitivity, specificity 73.9%, positive prediction value 73.1%, and negative prediction value 70.8%.Conclusion: The RDW/platelet ratio can be used as a noninvasive diagnostic test of liver fibrosis in chronic hepatitis B patients.